Three-Color Single-Molecule FRET and Fluorescence Lifetime Analysis of Fast Protein Folding - Yoo, Janghyun (J Phys Chem B, 2018)
We describe the theory, experiment, and analysis of three-color Förster resonance energy transfer (FRET) spectroscopy for probing conformational dynamics of a fast-folding protein, α(3)D. In three-color FRET, site-specific labeling of fluorophores is required to avoid ambiguity resulting from various species with different combinations of labeling positions. To this end, we first attached two dyes to a cysteine residue and an unnatural amino acid, and then appended a cysteine residue to the C-terminus of the protein by the sortase-mediated ligation for attaching the third dye. To determine all three FRET efficiencies, we used alternating excitation of the donor and acceptor 1 with two picosecond-pulsed lasers. Since the folded and unfolded states are not distinguishable in binned fluorescence trajectories due to fast folding on a millisecond time scale, we used a maximum likelihood method that analyzes photon trajectories without binning the data. The extracted kinetic parameters agree very well with the previously measured parameters for the same protein with two-color FRET, suggesting the addition of the third fluorophore does not affect the folding dynamics of the protein. From the extracted fractions of acceptor photon counts, the FRET efficiencies for all three dye pairs were calculated after various corrections. They were compared with the FRET efficiencies obtained from the global analysis of two-color segments collected in the same experiment. The FRET efficiencies of the folded state from the three-color segments agree with those from the two-color segments, whereas the three-color and two-color FRET efficiencies of the unfolded state are different. This happens because fluctuations of all three inter-dye distances contribute to the FRET efficiency measured in three-color FRET. We show that this difference can be accounted for by using the Gaussian chain model for the unfolded state with the parameters obtained from the analysis of two-color segments. This result shows that three-color FRET provides additional information on the flexibility of molecules that cannot be obtained from a combination of two-color FRET experiments with three dye pairs. Using the delay times of photons from the laser pulse, fluorescence lifetimes were determined using the maximum likelihood analysis. The correlation between FRET efficiencies and lifetimes of the donor, acceptor 1, and acceptor 2 was visualized in two-dimensional FRET efficiency-lifetime histograms. These histograms can be used to demonstrate the presence of conformational dynamics in a protein.